Study on the influence of an underground low-light environment on human safety behavior. Issue 1 (2nd January 2022) - Li, Jing; Wang, Zhen; Qin, Yaru; Qi, Ruikang; Fu, Gui; Li, Baochang; Yang, Lei
Abstract : Objective. This study aimed to research the impact that a coal mine lighting environment has on human safety behavior in an underground coal mine. Methods. We built a coal mine lighting simulation experiment system including both general lighting and local lighting divided into six different illumination gradients (0, 10, 30, 50, 75 and 100 lx) to test and analyze the effects of general illumination gradients on human fatigue, attention, reaction and eye–hand coordination with SPSS version 22.0. Results . Illuminance has a significant effect on human fatigue, attention, reaction ability and eye–hand coordination ability. Specifically, human fatigue is negatively correlated and the other indicators are positively correlated with the increase of illuminance. Notably, attention distribution ability seems to be most significantly influenced by illuminance according to this study, followed by human fatigue, reaction and eye–hand coordination ability. Conclusion. The results of the study indicate that illumination of the general lighting environment is expected to be controlled at a gradient of at least 50–75 lx or above in the coal mine environment where there is both general lighting and local lighting to reduce the incidence of accidents.